Implementation of BLE and LoRa Communication Channels on monitoring system Fish Pond Water Level in Rural areas Based Internet of Things - Pardede, Morlan; Sirait, Regina; Hutajulu, Elferida; Banurea, Waldemar (Bahasa Indonesia, 2024)
This study designs and develops a water level monitoring system for fish ponds based on the Internet of Things (IoT) using wireless communication channels Bluetooth low energy (BLE) and Lo-Ra The system consists of a Sensor Node, Repeater, Gateway, and the Blynk Cloud application. The Sensor Node detects the water level and pump condition, processes the data, and transmits it to the Repeater via BLE signals. The Repeater receives information from the Sensor Node and sends it to the Gateway using Lo-Ra signals. The Gateway receives the data and send it to the Blynk Cloud via WiFi and cellular networks. To conserve battery usage on the Repeater, the transmission process is scheduled periodically, where after sending information to the Gateway, the ESP-32 enters deep sleep mode for 60 seconds before resuming operation. Based on testing, the JSN-SR04T ultrasonic sensor can measure pond water levels ranging from 20 cm to 200 cm with a maximum error of 3% and an average error of 1%. The communication range of BLE in LOS (Line of Sight) areas with a 7dBi antenna can reach up to 40 meters, while the communication range of LoRa can reach up to 700 meters. By utilizing deep sleep mode on the Repeater to delay delivery battery usage is significantly more efficient compared to using the delay function, where a delivery delay of 60 seconds saves 143% and the longer the delay, the more economical the use of deep sleep. The water level and pump condition messages from the Sensor Node to the operator via Blynk vary between 8 to 25 seconds, depending on the internet signal.